Spatial Zonation Model of Local Irrigation System Sustainability (A Case of Subak System in Bali) - I Putu Sriartha; Sri Rum Giyarsih (Faculty of Geography, Universitas Gadjah Mada, 2015)
This study was aimed at designing a spatial zonation model of a subak sustainability type based on the internal and external dimentions from 69 subaks in three districts in Badung regency. The internal dimention was measured based on subak capability index in implementing Tri Hita Karana (THK) philosophy. The external dimention was measured by using index of four variables, namely: road density, population density, social economic facilities, and number of nonfarmer families.The data were analyzed using descriptive quantitative technique and spatial analysis using Geographical Information System (GIS) software. The results found three zones of subak sustainability type, spatially follows the principle of distance decay of the growth of tourism and city center. Unsustainable - less sustainable subak zone dominates short distance zone, sustainable - less sustainable subak zone dominates transitional zone, while sustainable subak zone dominates long distance zone. To protect subak from destruction, less sustainable subaks have to be restored into sustainable ones and the sustainable subaks should be made eternal/exclusive subaks